New measurement method for long-term oral complications after harvesting buccal mucosa grafts for urethroplasty - S. Farahzadi; M. Buckova; M. Von Witzleben; T. A. Schröder; G. Lauer; P. Korn (Head & Face Medicine)
Abstract Background Patients undergoing oral mucosa harvesting for urethroplasty may experience several challenges during recovery like scarring or changes in oral sensitivity, which can lead to long-term discomfort. In this retrospective study long-term donor site complications after harvesting of oral mucosa for urethroplasty were evaluated and a new measurement method for oral volume differences between the non-operated and operated sides was applied. Methods Thirty adult male patients who underwent urethroplasty with buccal mucosa grafting were included. At a median of 43 months after surgery, a standardized questionnaire was used, and clinical examinations were conducted to measure the postoperative elasticity of the buccal mucosa. This measurement compared the non-operated side with the operated side. Additionally, we examined descriptive statistics and the influence of smoking status, diabetes mellitus, immunosuppression, alcohol consumption, and graft size. Results In total, 36% of the patients reported persistent subjective postoperative impairments, such as tightness in the oral cavity or numbness. In all patients, a difference in buccal volume was observed between the operated side and the non-operated side. This volume difference ranged from 3 to 15 ml (mean 8.10 ml, SD ± 3.4; p < 0.001). As the size of the harvested transplant increased, the postoperative buccal volume difference also increased significantly (p < 0.001). In one patient, follow-up surgery was required due to the severity of scarring. The presence of diabetes mellitus, immunosuppressive medication, smoking status, and alcohol consumption had no statistically significant effect on postoperative buccal elasticity or mouth opening. Conclusions The use of buccal mucosa grafts for urethroplasty is an established procedure in urology, but the oral harvesting procedure can lead to scarring within the buccal area, which is associated with a statistically significant decrease in buccal volume compared with the non-operated site. The volume analysis was performed by applying a new measurement method, which enables, for the first time, the quantification of oral donor site morbidity.